Nonlinear control of an active heave compensation system - Do, Khac Duc; Pan, J. (Pergamon, 2008)
Heave motion of a vessel or a rig has an adverse impact on the response of a drill-string or a riser. To compensate for heave motion, passive and active devices are usually used. Active heave compensators, in which a control system is an essential part, allow conducting operations under more extreme weather conditions than passive ones. This paper presents a constructive method to design a nonlinear controller for an active heave compensation system using an electro-hydraulic system driven by a double rod actuator. The control system reduces the effect of the heave motion of the vessel on the response of the riser by regulating the distance from the upper end of the riser to the seabed. The control development is based on Lyapunov's direct method and disturbance observers. The paper also includes a method to select the control and disturbance observer gains such that actuator saturations are avoided. Stability of the closed loop system is carefully examined. Simulation results illustrate the effectiveness of the proposed control system. © 2007 Elsevier Ltd. All rights reserved.